2021
DOI: 10.3390/cancers13225787
|View full text |Cite
|
Sign up to set email alerts
|

Deep Convolutional Neural Networks Detect Tumor Genotype from Pathological Tissue Images in Gastrointestinal Stromal Tumors

Abstract: Gastrointestinal stromal tumors (GIST) are common mesenchymal tumors, and their effective treatment depends upon the mutational subtype of the KIT/PDGFRA genes. We established deep convolutional neural network (DCNN) models to rapidly predict drug-sensitive mutation subtypes from images of pathological tissue. A total of 5153 pathological images of 365 different GISTs from three different laboratories were collected and divided into training and validation sets. A transfer learning mechanism based on DCNN was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…However, the performance of our model decreased from center 1 to center 2. This is probably related to the small size of our training set as the lack of diversity in small cohorts often leads to poor transferability of deep learning models due to domain shift 19 22 . Indeed, a shift in risk prediction was observed when applying our model in the testing cohort, resulting in an under estimation of patients’ risk of relapse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the performance of our model decreased from center 1 to center 2. This is probably related to the small size of our training set as the lack of diversity in small cohorts often leads to poor transferability of deep learning models due to domain shift 19 22 . Indeed, a shift in risk prediction was observed when applying our model in the testing cohort, resulting in an under estimation of patients’ risk of relapse.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the tumor cell morphology can only partially explain the mutational profile, and DL learns additional morphological features related to mutations. With this unprecedented large cohort of patients, the model performance and robustness have been greatly improved for predicting mutations at gene level compared to a previous study 19 . More importantly, DL was able to accurately predict mutations that have a great impact in patients’ treatment decision and prognostic estimation such as PDGFRA exon18 D842V mutation which is a predictor for imatinib resistance and avapritinib 25 sensitivity, and KIT del-inc 557/558 mutations which are associated with a worse prognosis and high-risk of relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying these mutations is vital as there is specific therapy for them [ 69 , 70 ]. A CNN model was proposed by Liang et al (2021) [ 42 ] to identify the KIT and PDGFRA gene mutations based on the histologic images. Pre-trained models on ImageNet were used to predict these drug-sensitive mutations.…”
Section: Mutation Identificationmentioning
confidence: 99%
“…Successful instances include polyp classification in colonoscopy 26 and genotype evaluation in gastrointestinal stromal tumors. 27 With respect to stroke estimation, a multicenter study suggested using deep learning to predict ischemic stroke lesions from MRI. 28 Noncontrast computed tomography was also proposed in the literature to detect strokes by deep learning features due to its efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of computer‐aided diagnosis (CAD) systems, quantitative image features can be extracted and combined in a machine learning classifier to provide an objective and consistent diagnostic evaluation. Successful instances include polyp classification in colonoscopy 26 and genotype evaluation in gastrointestinal stromal tumors 27 . With respect to stroke estimation, a multicenter study suggested using deep learning to predict ischemic stroke lesions from MRI 28 .…”
Section: Introductionmentioning
confidence: 99%